2022
DOI: 10.1002/nur.22291
|View full text |Cite
|
Sign up to set email alerts
|

An examination of primary health care nursing service evaluation using the Donabedian model: A systematic review

Abstract: Nurses are key to the delivery of global primary health care services. However, there appears to be a lack of evaluation of primary health care nursing delivery models in the published literature. This evaluation is vital to the improvement of patient experiences, national and global health outcomes, and the justification of future investment in primary health care nursing services. The purpose of this review was to explore and analyze the literature that reports on the evaluation of primary health care nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The review instead focused on patient satisfaction, quality of life, self‐ efficiency and improvement in health behaviours post nursing interventions for chronic disease prevention and management such as screening, health education, wellness, physical activity and pathology testing (Lukewich et al., 2022). In addition, evaluation of the contribution to quality care made by nurses in primary health care services has been found to be lacking with preference given to medical outcome measures such as diagnosis of specific conditions, prescription costs and health outcomes (McCullough et al., 2023). The lack of research is likely related to the lack of data collected within existing data sets such as Medicare (primarily documenting medical activities with some nurse practitioner activities collected) and the nationally collected Practice Incentives Program Quality Improvement Measures (PIPQIM) (Australian Institute of Health and Welfare, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review instead focused on patient satisfaction, quality of life, self‐ efficiency and improvement in health behaviours post nursing interventions for chronic disease prevention and management such as screening, health education, wellness, physical activity and pathology testing (Lukewich et al., 2022). In addition, evaluation of the contribution to quality care made by nurses in primary health care services has been found to be lacking with preference given to medical outcome measures such as diagnosis of specific conditions, prescription costs and health outcomes (McCullough et al., 2023). The lack of research is likely related to the lack of data collected within existing data sets such as Medicare (primarily documenting medical activities with some nurse practitioner activities collected) and the nationally collected Practice Incentives Program Quality Improvement Measures (PIPQIM) (Australian Institute of Health and Welfare, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The responsibility of registered nurses in identifying and preventing patient deterioration extends beyond the hospital context to primary and community care or the out-of-hospital context (AIHW, 2020). In this context, nurses and midwives often work in multidisciplinary teams with people across the lifespan in an environment of limited resources (McCullough et al, 2023).…”
Section: What Does This Paper Contribute To the Wider Global Community?mentioning
confidence: 99%
“…Applied to the health care context (e.g., Körner et al, 2015), the framework depicts structures where an input affects a process that is likely to affect an output. The IPO framework shares a number of similarities with the structure–process–outcome framework (Donabedian, 1988) extensively used in the health care literature as a theoretical and structural framework for empirical (e.g., Kunkel et al, 2007) and review (e.g., McCullough et al, 2023) studies. In the respective frameworks, input and structure refer to the professional and organizational resources associated with the provision of care (Ameh et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…McCullogh et al (2023) conducted a systematic review of studies of primary health care nursing services, including NP practice, and found a paucity of research focused on nurse‐led services. What they did find was that the evaluation of these services reflected the medical model with the criteria of diagnosis rates, prescription costs, and disease outcomes.…”
Section: Nursingmentioning
confidence: 99%
“…McCullogh et al conclude that the unique contributions of nurses, including NPs, to care are not a part of the published research on the quality of care, particularly in primary health care. Therefore, issues incorporating personal care with health promotion, community empowerment, and patient participation are often excluded if the nursing lens is not applied (McCullogh et al, 2023).…”
Section: Nursingmentioning
confidence: 99%